Dental rehabilitation of a patient with a decrease in bite height due to pathological abrasion of hard tooth tissues (clinical case) - Sokolovska, V.M.; Tsvetkova, N.V.; Davydenko, V.Y.; Pysarenko, O.A.; Tarashevska, Y.E. (Medicni Perspektivi, 2024)
At the present stage of diagnostics and treatment of dental diseases, morphofunctional disorders of the dento-maxillary system associated with a decrease in the height of occlusion are becoming more common. In the scientific literature, this pathological condition is described under the name "occlusion" that decreases. The reasons that cause it include partial or complete loss of teeth, irrational prosthetics and untimely restoration of dentition defects, doctors’ mistakes in the restructuring of the masticatory apparatus, and a generalized form of pathological abrasion of hard tooth tissues. The purpose of the study – demonstration of a clinical case of pathological abrasion of hard tissues of teeth with a decrease in bite height, complicated by defects in the dentition. Patient S., 47 years old, applied for orthopedic help with complaints of anatomical deformity, significant abration of teeth on the upper and lower jaws, increased sensitivity to various types of irritants, partial absence of teeth, impaired masticatory function, periodic clicking in the temporomandibular joint, aesthetic and phonetic defects. Based on the data obtained, we established the following diagnosis: generalized form of pathological abrasion of hard teeth tissues, subcompensated form of reduced bite height, complicated by defects in the dentition of the upper jaw – class I according to the Kenedy classification, lower jaw – class III according to the Kenedy classification. The loss of chewing efficiency according to Agapov was 68%. Patient S. was recommended a two-stage orthopedic treatment, which involves preliminary separation of the bite with the help of individual vinyl mouth guards which have an increasing thickness of 2, 4 and 6 mm, made for the lower jaw.The planned treatment period with each of the muscle relaxant splints will be 2 months. Subsequently, 15, 14, 13, 12, 11, 21, 22, 23, 24 will be restored with one-piece metal crowns with ceramic cladding, and the final defects in the lateral areas will be restored with a clasp prosthesis with a locking system of fixation. The included defect of the lateral part of the lower jaw is planned to be restored with a metal-ceramic bridge-like prosthesis with a support on 47, 45, 44, and the worn-out hard tooth tissues will be completely restored with photopolymer material. In patients with a reduction in bite height of more than 2 mm, it is advisable to carry out treatment in two stages. At the first stage, we normalize the occlusal height and rebuild the function of the masticatory muscles. At the second stage, we provide rational prosthetics. Orthopedic rehabilitation with myorelaxing splints of increasing thickness makes it possible to correctly rebuild myostatic reflexes and prevent functional disorders in the TMJ. Any case of complex treatment of patients with a decrease in bite height due to pathological abrasion of the hard tooth tissues deserves the attention of both scientists and dentists in practical health care.